2013
DOI: 10.2139/ssrn.2253246
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and Incentives

Abstract: We study whether compensating people who volunteer to be leaders in a public goods game creates a social crowding-out effect of moral motivation among the others in the group. We report from an experiment with four treatments, where the base treatment is a standard public goods game with simultaneous contribution decisions, while the three other treatments allowed participants to volunteer to be an "early contributor" in their group. In the three leader treatments, we manipulate the level of compensation given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…In contrast, our 3 The experiment in Glöckner et al (2011) shows that followers respond to leaders more strongly when contributing is not a dominant strategy for leaders. Similar evidence is provided by Cappelen et al (2016) and van der Heijden et al (2013), who suggest that leaders' influence on followers is weak when leaders get a high compensation for leading or have no cost of setting good examples. endogenous treatment is based on volunteering for leadership.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…In contrast, our 3 The experiment in Glöckner et al (2011) shows that followers respond to leaders more strongly when contributing is not a dominant strategy for leaders. Similar evidence is provided by Cappelen et al (2016) and van der Heijden et al (2013), who suggest that leaders' influence on followers is weak when leaders get a high compensation for leading or have no cost of setting good examples. endogenous treatment is based on volunteering for leadership.…”
Section: Introductionsupporting
confidence: 69%
“…Our treatment with self-selected leaders also adds to the literature on endogenous leadership (e.g., Arbak & Villeval, 2013;Bruttel & Fischbacher, 2013;Cappelen et al, 2016;Dannenberg, 2015;Haigner & Wakolbinger, 2010;Préget et al, 2016;Rivas & Sutter, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…limiting their autonomy) had an adverse effect of the latter´s proclivity to cooperate. Cappelen et al (2016) and Aquino et al (1992) respectively observed that increasing the compensation given to the leader or allowing the leader to benefit without contributing attenuated cooperation by contravening distributive fairness and equality norms.…”
Section: Related Literaturementioning
confidence: 99%
“…Balliet et al, 2011;Drouvelis et al, 2015). Preliminary experimental studies suggest that endowing delegated managers with such discretionary rights would appear to provoke resentment, incite disobedience, and so forth (Nikiforakis et al, 2014;Cappelen et al, 2016), which not only undermines worker cooperative propensities, but ultimately sabotages the interests of the organization itself, and thereby, its residual claimant shareholders (Einarsen et al, 2007). This raises the question of how to design discretionary mechanisms in hierarchical organizations in order to circumscribe the scope of managerial self-seeking behavior vis-à-vis their subordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Psychologists have been overall more optimistic than economists in the effectiveness of rewards in sustaining cooperation, with Rand et al (2009) being a notable example. For a meta-analysis on the effectiveness of punishment and rewards including studies both from the literatures in economics and psychology, see Balliet et al (2011). 2013; Cappelen et al 2016;Preget et al 2016;Gächter and Renner, 2018). However, as these studies focus on leading by example, our study is only notionally related.…”
Section: Introductionmentioning
confidence: 99%